2007
DOI: 10.1158/1078-0432.ccr-06-1432
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Sorafenib in Combination with IFN α-2a in Patients with Unresectable and/or Metastatic Renal Cell Carcinoma or Malignant Melanoma

Abstract: Purpose: To determine the safety, maximum tolerated dose, pharmacokinetics, and efficacy, and to evaluate biomarkers, of the multikinase inhibitor sorafenib plus IFN a-2a in advanced renal cell carcinoma (RCC) or melanoma. Experimental Design: Patients received 28-day cycles of continuous, oral sorafenib twice daily and s.c. IFN thrice weekly: sorafenib 200 mg twice daily plus IFN 6 million IU (MIU) thrice weekly (cohort1); and sorafenib 400 mg twice daily plus IFN 6 MIU thrice weekly (cohort 2); or plus IFN 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 42 publications
6
79
0
4
Order By: Relevance
“…Cell proliferation of murine melanoma B16F10 cells was determined by MTT assay kit (Beyotime Institute of Biotechnology, Haimen, China) according to the manufacturer's protocol. B16F10 cells (1x10 4 ) were plated on 96-well culture plates and co-cultured with different concentrations (0-10 µM) of propofol (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany; Fig. 1) for 24 or 48 h at 37˚C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proliferation of murine melanoma B16F10 cells was determined by MTT assay kit (Beyotime Institute of Biotechnology, Haimen, China) according to the manufacturer's protocol. B16F10 cells (1x10 4 ) were plated on 96-well culture plates and co-cultured with different concentrations (0-10 µM) of propofol (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany; Fig. 1) for 24 or 48 h at 37˚C.…”
Section: Methodsmentioning
confidence: 99%
“…There is a rising trend in the number of melanoma cases worldwide (3). Among the industrial cities in South China, the morbidity of melanoma is much higher compared with the Chinese average rate, due to complex environmental factors (4).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, sorafenib can enhance the effects of radiation, rapamycin, and the small-molecule inhibitor ABT-737, which inhibits the Bcl-2 protein (18)(19)(20). In phase I and II studies, melanoma patients treated with sorafenib combined with carboplatin and paclitaxel, temozolomide, dacarbazine, or IFNα-2a showed a greater response compared with historical control and, in one study of dacarbazine alone, with little enhancement of toxicity (14,(21)(22)(23). To date, however, no studies have examined whether sorafenib can augment the response to the alkylating agents melphalan and temozolomide in the unique setting of regional therapy of advanced in-transit melanoma using either isolated limb infusion (ILI) or isolated limb perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first trials confirmed its efficacy in advanced, metastasized renal cell carcinoma, but only after immunotherapy with interleukin (IL)-2 and interferon (IFN)-alpha. 5 This highlights the need for a combined therapy, that uses immunotherapy together with tyrosine kinase inhibitors to target not only the cancer cell, but also the cancer microenvironment. This is of very special importance, as these drugs may indeed affect the malignant cell, but they also disrupt the local cancer niche, as proven by the very recent paper of Zhang et al 6 The group stated that sorafenib may actually kill some of the cancer cells, but it also promotes the dissemination of the cancer due to its "off target" effects on the niche, especially on the NK cells.…”
Section: Dear Editormentioning
confidence: 99%